"Females are always dominated and disregarded by males, just because they are female": the continuation of patriarchal norms for young trafficked women in Nepal. Issue 10 (2nd August 2022) - Ong, Tricia; Mellor, David; Chettri, Sabrina
Abstract: This article provides insights into the cultural aspects of sexual violence against young women trafficked into the sex industry in Nepal. Participant observation, participatory clay body mapping workshops and group interviews using photography were used to explore the reproductive body of six formerly trafficked women aged 14-22 years. Intimate partner violence against women, domestic violence and violence against women were important issues raised during the research process. Societal and familial patriarchal norms are the root causes of violence against women in Nepal and can be traced back to the Hindu legal code, the Muluki Ain of 1854, which was enforced for over 100 hundred years. Our findings indicate that tackling violence against women is complex for Nepali trafficked women because of its multiple forms and sources.